The Influence of Whatsapp Social Media, Parental Supervision, and Youth and Adolescent Lifestyles on Drug and Addictive Substance Use in Manado City - Kawengian, Debby D.V.; Kalesaran, Edmon Royan (Journal La Edusci, 2024)
The problem of drug use is one of the problems often experienced by young people and adolescents. In fact, if you see the potential of the younger generation is the hope of the Nation, because youth and adolescents are the successors of the ideals and struggles of the Nation. This study aims to: 1). Want to know the influence between WhatSapp social media on the use of Drugs and Addictive Substances in Manado City, 2). Want to know the Influence between Parental Supervision on the use of Drugs and Addictive Substances in Manado City, 3). Want to know the Influence between Youth and Adolescent Lifestyles on the use of Drugs and Addictive Substances in Manado City, 4). Want to know the influence between WhatSapp Social Media Use, supervision of people and lifestyles of youth and adolescents against the use of drugs and addictive substances in Manado City. The method used in this study is a quantitative method while the data analysis technique is carried out with the help of SPSS 26 of 2023. From the results of this study proves that: 1). There is a significant influence between the use of WhattShapp social media with the use of Drugs and Addictive Substances. 2). There is a significant effect between parental supervision and drug use and addictive substances, 3). There is a significant influence between lifestyle and drug use and addictive substances, 4). Together, there is an influence between WhattShapp Social Media Use, parental supervision and lifestyle on Drug and Addictive Substance Use.